2019
DOI: 10.1002/eco.2087
|View full text |Cite
|
Sign up to set email alerts
|

Proposals for optimizing sea lamprey passage through a vertical‐slot fishway

Abstract: Movement of sea lamprey through a vertical-slot fishway (built at the Coimbra dam, in central Portugal) was continuously monitored between 2013 and 2016 by a video recording system. Visual count data were used to quantify the overall successful movements and identify seasonal and circadian patterns of fishway use. Explicative models (Boosted Regression Trees) were used to study the relationship between frequency of successful movements during the species migration peak and environmental variables. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
3
11
0
Order By: Relevance
“…The monitoring approach employed in this study revealed crucial information regarding shad upstream migration, and this was accomplished without manipulating individuals and with no associated mortality or impact in behaviour, proving itself adequate to fulfil the goals established. It also confirmed that relatively large numbers of shad use the vertical slot fish pass at Coimbra dam, proving this structure built in 2011 can also be considered a successful habitat rehabilitation measure for shads as well as for sea lamprey (Pereira et al, 2017, 2019). During the study period (2013–2017), over 26,000 Alosa sp.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…The monitoring approach employed in this study revealed crucial information regarding shad upstream migration, and this was accomplished without manipulating individuals and with no associated mortality or impact in behaviour, proving itself adequate to fulfil the goals established. It also confirmed that relatively large numbers of shad use the vertical slot fish pass at Coimbra dam, proving this structure built in 2011 can also be considered a successful habitat rehabilitation measure for shads as well as for sea lamprey (Pereira et al, 2017, 2019). During the study period (2013–2017), over 26,000 Alosa sp.…”
Section: Discussionmentioning
confidence: 70%
“…(e.g., Acolás et al, 2004, 2006) and ecological modelling of spatial distribution (e.g., Nachón et al, 2016; Taverny et al, 2012; Trancart et al, 2014). BRTs have proven to be useful and to produce better results than other modelling techniques in the understanding and prediction of spatial distribution of fish (e.g., Bangley et al, 2020; Ferreira et al, 2013; Segurado et al, 2015); however, their application in the study of temporal distribution is less frequent (Escalle et al, 2016; França & Cabral, 2015; Pereira et al, 2019; Pittman & Brown, 2011). Furthermore, to our knowledge, the use of BRTs to model fish pass use and the environmental factors influencing its successful negotiation is a recent approach to these problems and may bring new insights on the matter (Pereira et al, 2019), especially due to its capacity to deal with missing data, outliers, different types of variables and non‐linear relationship between response and explanatory variables, which render the use of other statistical tools inadequate (Elith et al, 2008; Escalle et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations